Traumatic extensor tendon dislocation in a boxer: a case study - Bents, R. T.; Metz, J. P.; Topper, S. M. (Medicine & Science in Sports & Exercise, 2003)
An elite collegiate boxer developed extensor tendon subluxation in the small finger of his dominant right hand. He was thought to have a radial sagittal band disruption and was allowed to complete his season with custom padding. Surgical exploration revealed intact sagittal bands with divergent dislocation of the two extensor tendons to the small finger with underlying capsular rupture. These lesions were repaired and he successfully returned to boxing. Soft tissue injuries to the dorsal MCP joint may involve the collateral ligaments, the sagittal bands, the extensor tendons, or the joint capsule. Symptoms usually involve persistent pain, swelling, and tendon subluxation or dislocation. Accurate recognition and treatment is crucial as nonoperative treatment is generally unsuccessful and surgical reconstruction is required for optimal return to function.